A Virtual Reality Exergame to Engage Adolescents in Physical Activity: Mixed Methods Study Describing the Formative Intervention Development Process - Farič, Nuša; Smith, Lee; Hon, Adrian; Potts, Henry W W; Newby, Katie; Steptoe, Andrew; Fisher, Abi (JMIR Publications, 2021)
BackgroundEarly adolescence (13-17 years) is a critical developmental stage for physical activity promotion. Virtual reality (VR) exergaming is a promising intervention strategy to engage adolescents in physical activity. ObjectiveThe vEngage project aims to develop a physical activity intervention for adolescents using VR exergaming. Here, we describe the formative intervention development work and process of academic-industry collaboration. MethodsThe formative development was guided by the Medical Research Council framework and included recruiting an adolescent user group to provide iterative feedback, a literature review, a quantitative survey of adolescents, qualitative interviews with adolescents and parents, inductive thematic analysis of public reviews of VR exergames, a quantitative survey and qualitative interviews with users of the augmented reality running app Zombies, Run!, and building and testing a prototype with our adolescent user group. ResultsVR exergaming was appealing to adolescents and acceptable to parents. We identified behavior change techniques that users would engage with and features that should be incorporated into a VR exergame, including realistic body movements, accurate graphics, stepped levels of gameplay difficulty, new challenges, in-game rewards, multiplayer options, and the potential to link with real-world aspects such as physical activity trackers. We also identified some potential barriers to use, such as cost, perceived discomfort of VR headsets, and motion sickness concerns. A prototype game was developed and user-tested with generally positive feedback. ConclusionsThis is the first attempt to develop a VR exergame designed to engage adolescents in physical activity that has been developed within a public health intervention development framework. Our formative work suggests that this is a very promising avenue. The benefit of the design process was the collaborative parallel work between academics and game designers and the involvement of the target population in the game (intervention) design from the outset. Developing the game within an intervention framework allowed us to consider factors, such as parental support, that would be important for future implementation. This study also serves as a call to action for potential collaborators who may wish to join this endeavor for future phases and an example of how academic-industry collaboration can be successful and beneficial.